Impact of a brief series of soccer matches on vascular conditions in youth women - Sugawara, Jun; Ogoh, Nana; Watanabe, Hironori; Saito, Shotaro; Ohsuga, Maki; Hasegawa, Tetsuya; Kunimatsu, Narumi; Ogoh, Shigehiko (Frontiers in Physiology, 2024)
BackgroundAccumulative excessive physical load elevates central arterial stiffness and smooth muscular tone of peripheral vascular beds in endurance athletes. The aim of this study was to test the hypothesis that a brief series of soccer matches would increase central arterial stiffness and arterial wave reflection from the periphery in young female football players.MethodsFifteen subjects (17.2 ± 0.7 years, mean ± SD) participated in four matches over five consecutive days (one match per day, with two consecutive days of matches followed by one rest day, repeated twice) in the Youth Girls Soccer Tournament, either as starters or substitutes. Heart rate, blood pressure (BP), and the second derivative of the photoplethysmogram (SDPTG) were assessed the night before and 4 h after each match. The ratios of the first and second descending waves to the first ascending wave of SDPTG (B/A ratio and D/A ratio) were calculated as indices of central arterial stiffness and peripheral wave reflection, respectively. The intra-individual relationship among interest variables was evaluated using the repeated-measures correlation analysis (rmcorr).ResultsPost-match D/A ratio, systolic and diastolic BP were lower compared to the pre-match value, while the B/A ratio did not change significantly. Heart rate was higher post-than pre-match. Rmcorr demonstrated significant intra-individual correlations of the D/A ratio with diastolic BP (rrm = 0.259, P = 0.008) and heart rate (rrm = −0.380, P< 0.001).ConclusionContrary to our hypothesis, a brief series of matches did not increase central arterial stiffness in young female football players. Instead, the matches induced a repeated, temporary attenuation of arterial wave reflection. This attenuated arterial wave reflection from the periphery appeared to be associated with reduced diastolic BP and a compensatory increase in heart rate.